Surrounded by Images and Meanings : Essays on Media and Cultural Studies - Habibi, Zaki (Penerbit Komunikasi UII, 2016)
Abstract This book consists of seventeen essays which are categorised into four sections: (1) the theoretical standpoint: semiotic and discursive approach, (2) news photography, television, and Internet in particular context, (3) cinema in contexts, and (4) documentary studies. The topics being discussed in all essays are varied, ranging from media in Asia, film and documentary studies, media and social activism, to cinema and psychoanalysis, as well as covering several concepts, such as class, identity, gender relations, textual analysis, text, context, meaning, and discourse. However, there is one central idea that connects all of them, i.e. offering the readers to detailed elaboration and application of concepts and theories in the field of media and cultural studies.